Arrangement of Submarine Cables and Pipelines as Part of Marine Spatial Planning in Indonesia - Rizka Iswara; Arie Afriansyah (Faculty of Law, Jambi University, 2022)
As a country with many islands, Indonesia is also surrounded by an ocean that is two-thirds wider than the territory of its own country. So Indonesia must be able to manage and organize the sea regularly to be used for the welfare of the people. Marine spatial planning is not only done to organize what is above the sea but also to organize what is under the sea. One of the activities used under the sea is laying submarine cables and pipelines used for various sectors. There are many irregularities in laying submarine cables and pipelines in the Indonesian sea conditions. It can lead to fatal accidents at sea and damage the facilities needed by the community, so a comprehensive and integrated arrangement is required. In addition to preventing maritime accidents, marine spatial planning can also serve as a reference and guide for all parties using the ocean to prevent conflicts between users. Marine spatial planning is also the primary foundation to support and realize Indonesia's ideals as the Global Maritime Fulcrum. This study examines several existing regulations related to the arrangement of submarine pipelines/cables in Indonesia. It finds several problems where some aspects have not been regulated in the regulation. This research provides recommendations on these problems by looking at the needs of stakeholders for the implementation of an orderly Indonesian marine layout.